Malaria due to Plasmodium knowlesi in South-Eastern Asia and America. May imported cases represent a health care alert? - Sabbatani, Sergio; Fiorino, Sirio; Manfredi, Roberto (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2012)
Four main malaria plasmodia involve human beings. Plasmodium vivax, Plasmodium malariae and Plasmodium ovale had an older evolution paralelling the human species evolution (co-evolution), while Plasmodium falciparum has been encountered by humans later during their evolution, since it was acquired by monkeys probably between the end of Mesolithicand the beginning of Neolithic eras.